Pengaruh Pola Asuh Ibu terhadap Tingkat Kesadaran Kesetaraan Gender - Nanik Kholifah (Ilmu Psikologi Universitas Yudharta Pasuruan)
Gender equality is something that is expected of women. gender equality is not only seen in mature adult women's lives, but also in the lives of young women. The purpose of this study was to determine the effect of parenting, on the level of awareness of gender equality in young women. The population of this study is high school student in Pandaan sub-district. Samples were used as many as 30 students, by using purposive non random sampling technique. Information gathering uses observation, interview, and attitude scale. as many as 44 items on an attitude scale on gender equality awareness, obtained 23 valid items with a biserial point correlation coefficient between 0.3049 to 0.4959 and a reliability coefficient of 0.7054. Out of 44 items of maternal parenting scale 22 items were valid, with a biserial point correlation coefficient between 0.3412 to 0.5407 and a reliability coefficient of 0.7305. Information analysis was calculated using a single predictor regression analysis and obtained a value of F = 0.1026 with F tab 5% of 4.18. So F count <F tab 5%. This means that there is no influence of parenting on the level of awareness of gender equality in young women.